Synthesis of hydroxyapatite and strontium-substituted hydroxyapatite for bone replacement and osteoporosis treatment - Bang, Le Thi; Ha, Nguyen Van; Long, Bui Duc; Hong Nhung, Nguyen Thi (Vietnam Journal of Science and Technology, 2024)
Hydroxyapatite (HAp) is an inorganic component exhibiting bioactivity similar to that of natural bone. However, it is not resorbed by osteoclasts during bone remodelling due to its lack of bio-resorption property. This can be enhanced by the substitution of other element presented in bone mineral. In this research work, hydroxyapatite (HAp) and strontium-substituted hydroxyapatite (Sr-HAp) were synthesized by a precipitation method. Calcium nitrate tetra hydrate [Ca(NO3)2•4H2O], disodium hydrogen phosphate (Na2HPO4), and Strontium nitrate [Sr(NO3)2] were used as Ca, PO4 and Sr sources, respectively. Molar ratio Ca/P=1.67 was used to synthesize HAp, where (Ca+Sr)/P=1.67 was used to synthesize strontium substituted-HAp (Sr-HAp). The reaction was carried out at room temperature. The results show that pure HAp and Sr-HAp were formed with nanometer-sized particles. Sr substitution in the HAp lattice results in an increase in both the lattice disorder and crystal aspect ratio. The results of in vitro bioactive testing using simulated bodily fluid also showed that both HAp and Sr-HAp have high bioactive, with the Sr-HAp sample having the greater bioactive. Therefore, HAp and Sr-HAp have great potential for biological applications.